THE DEVELOPMENT OF SCIENCE FICTION AS A LITERARY GERNE - Yuldasheva Mahinur Baxodir qizi; ABDURAMONOVA DIANA VALERYEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: Numerous historical, cultural, and technological developments have influenced  the  evolution  of  science  fiction  as  a  literary  genre.  Science  fiction  first appeared in the 19th century as a speculative examination of scientific discoveries and their possible repercussions, as seen by works such as Mary Shelley's *Frankenstein* and  H.G.  Wells' *The  War  of  the  Worlds*.  The genre developed  into a  variety  of subgenres,  including  cyberpunk,  dystopian  fiction,  and  space  opera,  as  a  result  of changes  in  society,  politics,  and  science  over  time.  The  genre  began  to  explore questions of identity, morality, and the human condition in a world that was becoming more complex, rather than just picturing futuristic technologies.